Proposed new interior design of Justlife Retail for Justlife Group Sdn. Bhd. at LOT B-1-1-16 & B-1-1-18.First Floor,BBT One Boulevard,Lebuh Batu Nilam 2, Bandar Bukit Tinggi,41200,Klang Selangor / Putri Juwita Mohamed Noor - Mohamed Noor, Putri Juwita (Faculty of Architecture, Planning and Surveying, 2010)
A final year student of Diploma in Interior Design is required to prepare their own final year project. Each student may have a brand new ideas on designing their proposed project. The project proposal report proposed herein, is a new interior design of Kingsmen Malaysia’s new office at Lot 12, Jalan Taming 2, Taman Perindustrian Selesa Jaya, 43300 Balakong, Selangor. Kingsmen Sdn Bhd is a well known communication design and production group in Asia Pacific and in Malaysia. Established in 1983, it providies turnkey solutions in design, project management, roll-out management, custom fixture manufacturing, general contracting, outsourcing and fulfillment, warehousing and logistics management. Currently Kingsmen’s number of staff and load of works increase tremendously as a private company with 104 workers, 9 directors and 5 departments. Kingsmen’s Malaysia may widen its relationship with clients and they usually visit the office for further discussions or for business purposes. Throughout the proposed new office, Kingsmen’s Malaysia will stand tall to its reputation and standard along with its image. With that in mind. They need a bigger area to strive for further success and a site has been determined for this new proposed office which is in accordance to Kingsmen’s conditions and needs. In this report, the whole new look and image of Kingsmen’s Malaysia are proposed smoothly according to the design process and material presented through readings, lecture and design projects. This proposal which reflects the whole new look of Kingsmen’s Malaysia new office covers every department beginning from the reception, workstations to staff lounge. It is proposed for Kingsmen to have the “ Transparent through Modernity * concept which is fully based on their company’s profile, design portfolio and company’s logo which is in grey and red letterings that defines a design-oriented approach to their business yet gives greater visibility in the market